2004
DOI: 10.1080/01411590310001637066
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Enzymes and Lipid Peroxidation in Different Stages of Breast Cancer

Abstract: Oxidative stress resulting from an imbalance between pro-oxidants and anti-oxidants seems to play an important role in human breast carcinogenesis. There are conflicting reports regarding the tissue levels of malondialdehyde (MDA), ascorbic acid and superoxide dismutase (SOD) in breast cancer patients whereas few blood values have been reported. The present study was carried out to observe the changes in serum MDA, serum SOD and plasma ascorbic acid with the stage-wise progression of the disease. Serum MDA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(55 citation statements)
references
References 16 publications
6
47
0
2
Order By: Relevance
“…8 Several studies have found enhanced lipid peroxidation and depletion of antioxidants in the plasma of BC patients, suggesting that increased oxidative stress may be related to human breast carcinogenesis. [9][10][11][12][13] Moreover, an increased content of lipid peroxidation products was found in BC tissue, supporting the hypothesis of breast tumorigenesis by in situ oxidative stress. 14,15 On the other hand, recent reports suggest that lipid peroxidation may represent a protective mechanism in BC through the induction of apoptosis, thereby maintaining the balance between breast epithelial cell growth and death, 8,16 supporting the hypothesis that lipid peroxidation in tissue of benign breast disease (BBD) is greater than in BC.…”
supporting
confidence: 71%
“…8 Several studies have found enhanced lipid peroxidation and depletion of antioxidants in the plasma of BC patients, suggesting that increased oxidative stress may be related to human breast carcinogenesis. [9][10][11][12][13] Moreover, an increased content of lipid peroxidation products was found in BC tissue, supporting the hypothesis of breast tumorigenesis by in situ oxidative stress. 14,15 On the other hand, recent reports suggest that lipid peroxidation may represent a protective mechanism in BC through the induction of apoptosis, thereby maintaining the balance between breast epithelial cell growth and death, 8,16 supporting the hypothesis that lipid peroxidation in tissue of benign breast disease (BBD) is greater than in BC.…”
supporting
confidence: 71%
“…Moreover, Madan et al [83] proved that the combination regimen containing chemotherapy in addition to vitamin E appears to be effective in normalizing amino transferases among nonalcoholic fatty liver disease suffering patients. The nutritional non-enzymatic antioxidants were increased in their serum levels in HCC patients as regards Nigella Sativa oil and fish oil supplementation when compared with control subjects this agree with data performed by Khanzode et al [84] they reported that the Zinc which is not a proper antioxidant but is an important cofactor incorporated into an intracellular antioxidant enzyme (superoxide dismutase) can ameliorate the dysfunction state occurring in HCC suffering individuals.…”
Section: Discussionsupporting
confidence: 89%
“…In some cases, there are differences between different antioxidants in the same patient; some increase and others decrease (Ray et al, 2000). In breast cancer, for example, several studies describe an increase of lipid peroxidation and a decrease of antioxidants (Khanzode et al, 2004;Sener et al, 2007). However, other studies performed in neoplastic tissues have shown a greater presence of ROS and a high expression of antioxidants (Oltra et al, 2001;Gönenç et al, 2006).…”
Section: Antioxidants In Oxidative Therapy Against Cancermentioning
confidence: 99%